MASALAH – MASALAH YANG DIHADAPI SISWA YANG MENONTON PORNOGRAFI DI SMPN 5 TANAH PUTIH - Hartati, Sri Hartati Sri; Umari, Tri Umari Tri (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
AbstractThis research entitle “ Problems of face Student that watch Pornografi in SMPN 5 Tanah Putih academic year 2013/2014” (by Sri Hartati, this NIM 1205188176). The purpose research is analyze describe  of problems face student that watch pornografi in SMPN 5 Tanah Putih academic year 2013/2014, based of general problem based of sex and base of very heavy problem or disturb that experience of man and woman students.This method have the character descriptive that is problems research that in research with describe object. Data collect tool is using in this research is AUM UMUM polling SLTP FORMAT 3 The populate of this research are students of  SMPN 5 Tanah Putih academic year 2013/2014 that amount 30 students there are 18  man and 12 woman and become research sample. Based analyze data of get conclusion that problem describe student watch pornografi in SMPN 5 Tanah Putih in general manner is self individual problem. Analyze student problem that watch pornografi in SMPN 5 Tanah Putih based sex, man and woman student have same problem there is self individual, there is man student that experience self individual much 47 % and woman student that experience self individual much 53 %. Analyze student problem that watch pornografi in SMPN 5 Tanah Putih that is showing heavy problem or disturb that man student experience is aspect, JDK,DPI,PDP,ANM and KHK . and that heavy problem woman student experience is JDK, DPI, HSO and ANM. KeyWord: General Problem, AUM UMUM, Student